Mitochondria inter-organelle relationships in cancer protein aggregation - Genovese, Ilaria; Fornetti, Ersilia; Ruocco, Giancarlo (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are physically associated with other organelles, such as ER and lysosomes, forming a complex network that is crucial for cell homeostasis regulation. Inter-organelle relationships are finely regulated by both tether systems, which maintain physical proximity, and by signaling cues that induce the exchange of molecular information to regulate metabolism, Ca2+ homeostasis, redox state, nutrient availability, and proteostasis. The coordinated action of the organelles is engaged in the cellular integrated stress response. In any case, pathological conditions alter functional communication and efficient rescue pathway activation, leading to cell distress exacerbation and eventually cell death. Among these detrimental signals, misfolded protein accumulation and aggregation cause major damage to the cells, since defects in protein clearance systems worsen cell toxicity. A cause for protein aggregation is often a defective mitochondrial redox balance, and the ER freshly translated misfolded proteins and/or a deficient lysosome-mediated clearance system. All these features aggravate mitochondrial damage and enhance proteotoxic stress. This review aims to gather the current knowledge about the complex liaison between mitochondria, ER, and lysosomes in facing proteotoxic stress and protein aggregation, highlighting both causes and consequences. Particularly, specific focus will be pointed to cancer, a pathology in which inter-organelle relations in protein aggregation have been poorly investigated.